Mouse Model of Devil Facial Tumour Disease Establishes That an Effective Immune Response Can be Generated Against the Cancer Cells - Pinfold, Terry L.; Brown, Gabriella K.; Bettiol, Silvana S.; Woods, Gregory M. (Frontiers in Immunology, 2014)
The largest carnivorous marsupial in Australia, the Tasmanian devil (Sarcophilus harrisii) is facing extinction in the wild due to a transmissible cancer known as Devil Facial Tumour Disease (DFTD). DFTD is a clonal cell line transmitted from host to host with 100% mortality and no known immunity. While it was first considered that low genetic diversity of the population of devils enabled the allograft transmission of DFTD recent evidence reveals that genetically diverse animals succumb to the disease. The lack of an immune response against the DFTD tumor cells may be due to a lack of immunogenicity of the tumor cells. This could facilitate transmission between devils. To test immunogenicity, mice were injected with viable DFTD cells and anti-DFTD immune responses analyzed. A range of antibody isotypes against DFTD cells was detected, indicating that as DFTD cells can induce an immune response they are immunogenic. This was supported by cytokine production, when splenocytes from mice injected with DFTD cells were cultured in vitro with DFTD cells and the supernatant analyzed. There was a significant production of IFN-γ and TNF-α following the first injection with DFTD cells and a significant production of IL-6 and IL-10 following the second injection. Splenocytes from naïve or immunized mice killed DFTD cells in in vitro cytotoxicity assays. Thus they are also targets for immunological destruction. We conclude that as an immune response can be generated against DFTD cells they would be suitable targets for a vaccine.